2009
DOI: 10.2353/ajpath.2009.080618
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Signaling in FIZZ1 Induction of Myofibroblast Differentiation

Abstract: Notch1 is an evolutionarily conserved receptor that regulates cell fate, including such events as differentiation, proliferation, and apoptosis. Myofibroblast differentiation is a key feature of lung fibrosis. Found in inflammatory zone 1 (FIZZ1) has direct fibrogenic properties because of its ability to induce myofibroblast differentiation. However, the downstream signaling pathway that mediates FIZZ1 induction of myofibroblast differentiation remains unknown. The objective of this study was to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 53 publications
5
105
0
3
Order By: Relevance
“…This led us to investigate the involvement of the Notch-signaling pathway, which has recently been reported to have an important role not only in EMT but also in pulmonary fibrosis. 27,35 Expression of some Notch ligands and receptors was upregulated by A771726, and an inhibitor for this pathway (DAPT) partially suppressed the A771726-induced EMT-like phenotypes, suggesting the involvement of the Notch-signaling pathway to this phenomenon. Furthermore, although it is known that A771726 has various activities other than inhibition of DHODH, including inhibition of tyrosine kinase and cyclooxygenase-2, 36,37 we clearly showed that the primary target of A771726 for induction of EMT is DHODH based on the following observations: (1) transfection of cells with siRNA for DHODH induced EMT-like phenotypes, (2) among the A771726 analogs, the ability to induce EMT-like phenotypes correlated with the ability to inhibit DHODH and (3) the addition of uridine to the culture medium completely suppressed the A771726-induced EMT-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This led us to investigate the involvement of the Notch-signaling pathway, which has recently been reported to have an important role not only in EMT but also in pulmonary fibrosis. 27,35 Expression of some Notch ligands and receptors was upregulated by A771726, and an inhibitor for this pathway (DAPT) partially suppressed the A771726-induced EMT-like phenotypes, suggesting the involvement of the Notch-signaling pathway to this phenomenon. Furthermore, although it is known that A771726 has various activities other than inhibition of DHODH, including inhibition of tyrosine kinase and cyclooxygenase-2, 36,37 we clearly showed that the primary target of A771726 for induction of EMT is DHODH based on the following observations: (1) transfection of cells with siRNA for DHODH induced EMT-like phenotypes, (2) among the A771726 analogs, the ability to induce EMT-like phenotypes correlated with the ability to inhibit DHODH and (3) the addition of uridine to the culture medium completely suppressed the A771726-induced EMT-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…25e31 Animal models, such as bleomycin-induced pulmonary fibrosis , are characterized by 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 both acute and chronic inflammation with subsequent myofibroblast differentiation that mainly originated from the mesenchymal compartment. 21,25e28 In vitro studies of cultured cells implicate Notch signaling in myofibroblast differentiation, 21 which is mediated by induction of the Notch1 ligand Jagged1 when lung fibroblasts are treated with found in inflammatory zone 1. 21 Moreover, GDP-4-keto-6-deoxymannose-3,5-epimerase-4-reductase knockout mice with defective fucosylation of Notch1 exhibit consequent impairment of Notch signaling and attenuated pulmonary fibrosis in studies using the bleomycin model.…”
mentioning
confidence: 99%
“…In contrast, lung epithelial cell-specific deletion of β-catenin results in blocked alveolar epithelial cell differentiation, resulting in a lung structure composed primarily of conducting airways, thus demonstrating a critical requirement of β-catenin for regular formation of alveoli (129). In IPF, the Wnt/β-catenin developmental network is one of the core signal signaling (93,(136)(137). Interestingly up to now, there is neither data on the Notch signaling pathway element expression in IPF nor on the influence of Notch activation on alveolar epithelial proliferation, differentiation or survival.…”
Section: H 24h and 48h 48hmentioning
confidence: 99%
“…The rationale for examining the Notch pathway in lung fibrosis does not exclusively stem from the knowledge of the influence of Notch on the regenerative response to injury in adult tissue (129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141) but also from a growing number of studies showing that Notch signaling may play a significant role in the process of fibrosis in organs such as kidney, skin and heart (95,98,142). In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144).…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosismentioning
confidence: 99%